2019
DOI: 10.1029/2018ja026190
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variations of Low‐Latitude Migrating and Nonmigrating Diurnal and Semidiurnal Tides in TIMED‐SABER Temperature and Their Relationship With Source Variations

Abstract: Seasonal and source variations of migrating and nonmigrating tides are studied using Thermosphere‐Ionosphere‐Mesosphere Energetics and Dynamics‐Sounding of the Atmosphere using Broadband Emission Radiometry temperature data at 10°N (5–15°N) for the year 2009. The migrating DW1 shows equinoctial maximum and summer minimum at low latitudes. It shows equinoctial asymmetry with larger amplitudes during spring equinox than fall equinox. The migrating semidiurnal tidal amplitude (SW2) shows larger amplitudes (~20 K)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 38 publications
2
25
0
Order By: Relevance
“…In April, QSPWs associated with the stratospheric final warming may again interact with SW2, whose growth recurs in Spring, to spawn SW1 and SW3. Alternatively, the non‐linear interactions between westward‐propagating diurnal tides of zonal wavenumbers 1 and 2 can theoretically lead to the seasonal climatological variation of SW3 (Sridharan, 2019), along with the changing tropospheric forcing below.…”
Section: A Comparison Of Superdarn and Sd‐waccm‐xmentioning
confidence: 99%
See 1 more Smart Citation
“…In April, QSPWs associated with the stratospheric final warming may again interact with SW2, whose growth recurs in Spring, to spawn SW1 and SW3. Alternatively, the non‐linear interactions between westward‐propagating diurnal tides of zonal wavenumbers 1 and 2 can theoretically lead to the seasonal climatological variation of SW3 (Sridharan, 2019), along with the changing tropospheric forcing below.…”
Section: A Comparison Of Superdarn and Sd‐waccm‐xmentioning
confidence: 99%
“…(1997), has been employed to extract climatological semidiurnal tides (e.g., Truskowski et al. (2014) and references therein) and their variations during SSW events (e.g., Sridharan, 2019). Single‐station observations can resolve the 12‐h tidal signature but, independently, cannot distinguish zonal wavenumbers.…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge of how natural forcings such as the solar cycle (SC), QBO, ENSO, and long-term changes in radiatively active gases (CO 2 , O 3 , CH 4 , N 2 O, chlorofluorocarbons) together affect the tidal amplitude is scarce. Although some studies have reported a link between the tidal variability and one or more of the above natural forcings (e.g., Dhadly et al, 2018;Gurubaran et al, 2005Gurubaran et al, , 2009Gurubaran & Rajaram, 1999;Hagan et al, 1999;Lieberman et al, 2007;Liu et al, 2017;Oberheide et al, 2011;Pedatella & Liu, 2012;Sridharan, 2019Sridharan, , 2020Sridharan et al, 2010;Trenberth et al, 2002;Vincent et al, 1998;Vitharana et al, 2019;Xu et al, 2009), they focus either on short periods or on a specific geographic location. Furthermore, none of these studies have looked at all of the different forcings combined.…”
Section: Introductionmentioning
confidence: 99%
“…They also noted the consecutive occurrence of counter electrojet events during the SSW of 2005. Sridharan (2019) observed enhancement of SW2 tide during northern hemispheric summer months and related it to similar ozone variations in the stratosphere. This could be the reason for the large occurrence of counter electrojet events during northern hemispheric summer months.…”
Section: Discussionmentioning
confidence: 87%